P.120 Contrast induced encephalopathy following endovascular therapy for the treatment of cerebrovascular disease. (June 2022) - MacLean, MA; Muradov, JH; Pickett, GE; Friedman, A; Weeks, A; Volders, D
Abstract : Background: Contrast induced encephalopathy (CIE) is an underrecognized, adverse effect of contrast administration during endovascular procedures. A paucity of literature exists regarding CIE following treatment of cerebrovascular disease. As such, we sought to describe our institutional experience with this entity. Methods: We searched our neurovascular database for instances of CIE following endovascular therapy for cerebrovascular disease. We extracted patient data, including demographics, comorbidities, procedural data, symptoms, radiological findings, and treatment. Informed consent was obtained in all cases. Data was analyzed using descriptive statistics. Results: Two patients underwent coiling of cerebral aneurysms; four were treated for ischemic stroke (thromboembolism or large artery atherosclerosis). Mean age was 67.2 years. Risk factors for microvascular dysfunction were identified for most patients: hypertension (100%), obesity (83%), dyslipidemia (83%), prior stroke (83%), renal disease (80%), and connective tissue disorders (33%). Mean operative duration: 284.5 minutes. Mean contrast volume: 285.7 mL. Decreased level of consciousness and lateralizing neurological deficits were the most common CIE-related symptoms. Treatments included intravenous fluids, corticosteroids, and anti-hypertensives. Radiographic findings included effaced cortical sulci, parenchymal edema, and cortical/subarachnoid contrast enhancement. Conclusions: Here, we describe our institutional experience with CIE following endovascular therapy for cerebrovascular disease. We hypothesize that CIE may be facilitated by pre-existing microvascular pathology.